Evaluation of Withania somniferaL.on oxidative stress and neuroinflammatory activities in rat’s brain by LPS induced cerebral palsy model - Chandrasekhar Thota; P. Muralidharan (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study explores the potential neuroprotective effects of Withaniasomnifera L. (Ashwagandha), which is recognized for its anti-inflammatory and antioxidant benefits. Adult Wistar rats were subjected to lipopolysaccharide (LPS) exposure and treated orally with the hydroalcoholic extract of Withaniasomnifera (HAEWS). The results indicated significant enhancements in motor functions and a reduction in cognitive impairments, pointing to improved learning and memory capabilities. Additionally, the study revealed decreased neuroinflammation and neuronal damage, highlighting the strong neuroprotective properties of Withaniasomnifera. This positions Withaniasomnifera as a promising therapeutic option for addressing cerebral palsy.